Pengaruh Lingkungan Kerja Fisik Terhadap Disiplin Kerja Guru Formal Madrasah Tsanawyah Bina Bangsa Di Pondok Pesantren Al-Falah Desa Suka Maju Kecamatan Sungai Lilin - Citra Dewi; Zunaidah Zunaidah; Afriyadi Cahyadi (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2019)
This study aims to determine and analyze how the physical work environment influences of formal teachers of Bina Bangsa Madrasah Tsanawiyah at Al-Falah Islamic Boarding School in Suka Maju Village, Sungai Lilin District. This research is a type of descriptive research using a questionnaire as a research instrument. Respondents used were the entire population of 40 people. The method used to analyze the influence of the physical work environment on teacher work discipline is simple linear regression analysis. Based on the research, it was found that the physical work environment had a positive and significant effect on the work discipline of formal teachers of Bsina Bangsa Madrasah Tsanawiyah. In order for the physical work environment and work discipline to be better, it is suggested that the Leader can provide good facilities in each classroom.